2022
DOI: 10.1080/21645515.2022.2112879
|View full text |Cite
|
Sign up to set email alerts
|

Reasons underlying the intention to vaccinate children aged 5-11 against COVID-19: A cross-sectional study of parents in Israel, November 2021

Abstract: Vaccination is a key tool to mitigate impacts of the COVID-19 pandemic. In Israel, COVID-19 vaccines became available to adults in December 2020 and to 5–11-year-old children in November 2021. Ahead of the vaccine roll-out in children, we aimed to determine whether surveyed parents intended to vaccinate their children and describe reasons for their intentions. We collected information on parental socio-demographic characteristics, COVID-19 vaccine history, intention to vaccinate their children against COVID-19… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Other factors included misconceptions about the severity of COVID-19 [73%; 95% CI: 73–79], efficacy and safety of vaccines [53%; 95% CI: 50 −56], parents’ young age [AOR:2.40; CI: 1.50–3.83], vaccination history [AOR: 16.47; CI: 8.39–32.33] and high fear among family members [AOR: 2.35; CI: 1.38–4.02]. 13 , 14 Misinformation leading to vaccination reluctance could endanger public health and make dealing with the current situation more difficult. 15 Studies also reported the potential role of healthcare providers (HCPs) to ensure evidence-based effective communication with parents about focused health education strategies to change their perception towards vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Other factors included misconceptions about the severity of COVID-19 [73%; 95% CI: 73–79], efficacy and safety of vaccines [53%; 95% CI: 50 −56], parents’ young age [AOR:2.40; CI: 1.50–3.83], vaccination history [AOR: 16.47; CI: 8.39–32.33] and high fear among family members [AOR: 2.35; CI: 1.38–4.02]. 13 , 14 Misinformation leading to vaccination reluctance could endanger public health and make dealing with the current situation more difficult. 15 Studies also reported the potential role of healthcare providers (HCPs) to ensure evidence-based effective communication with parents about focused health education strategies to change their perception towards vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…Given the uncertainty about the severity of the COVID-19 courses, premature conclusions by authorities on vaccination recommendations for a vulnerable group such as children should be discouraged. As trust is one of the major drivers for vaccine acceptance, valid and evidence-based information should be published and the government should aim to improve trust and reduce vaccine hesitancy [ 31 , 36 , 53 , 61 , 62 , 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another determinant very strongly associated with vaccination willingness was the pressure perception by COVID-19 vaccination campaigns ( r = 0.775; p adj < 0.05). Recent investigations examining vaccination willingness recommend providing additional detailed information and education about COVID-19 vaccination to increase knowledge and thus vaccination acceptance in the population, often through vaccination campaigns [ 26 , 36 , 53 , 63 , 65 ]. However, earlier findings of this study suggested elevated vaccination refusal among individuals who perceived increased pressure from vaccination campaigns and calls for COVID-19 vaccines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We did not find studies that included aspects of political affiliation among minority groups in Israel during the COVID‐19 pandemic. However, taking into account the political instability that is taking place in Israel during the last few years, it is possible that the complete willingness to be vaccinated could also be a question of political disregard against the Israeli government, especially among the Arab minority (Morozov et al, 2022). In this regard, it has been found that the trust level in the “system” (health directives and authorities) was significantly lower among Arabs as compared to Jews during the COVID‐19 pandemic in Israel.…”
Section: Perception Of Covid‐19 As a Health Threat Ptsd Burnout—and T...mentioning
confidence: 99%